2009
DOI: 10.1021/la9029672
|View full text |Cite
|
Sign up to set email alerts
|

Gecko-Inspired Combined Lamellar and Nanofibrillar Array for Adhesion on Nonplanar Surface

Abstract: We report the fabrication from a hard polymer of lamellar structures that act as base support planes for high-aspect ratio nanofiber arrays. We experimentally show that nanofiber arrays on lamellae can adhere to both planar and nonplanar surfaces, exhibiting 5 times greater shear strength on a 100 mum peak-to-peak grating than the arrays without the lamellar support structure. The observed behavior on nonplanar surfaces is attributed to the high compliance of the lamellar flaps. The compliance of the combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 26 publications
1
71
0
Order By: Relevance
“…1D and Movie S8, the soft system can increase the adhesion on a highly curved geometry smaller than the FAM and lift up a weight as much as it could with the full contact in Fig. 1 B and C. Unlike geckos' biological foot-hairs, synthetic microfibers are highly sensitive to surface roughness (46), requiring very smooth surfaces like glass for high adhesion. However, the soft system can enhance the weak adhesion of the microfibers on slightly rough surfaces such as cherry tomatoes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1D and Movie S8, the soft system can increase the adhesion on a highly curved geometry smaller than the FAM and lift up a weight as much as it could with the full contact in Fig. 1 B and C. Unlike geckos' biological foot-hairs, synthetic microfibers are highly sensitive to surface roughness (46), requiring very smooth surfaces like glass for high adhesion. However, the soft system can enhance the weak adhesion of the microfibers on slightly rough surfaces such as cherry tomatoes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Current synthetic gecko-inspired adhesives incorporate only micro-and nano-structures that adhere ideally to smooth surfaces, but few synthetic adhesives have incorporated macroscale structures similar to those found on gecko feet that would allow for adhesion on macroscopically rough surfaces (Ge et al, 2007). In one case, Lee et al fabricated nanofiber arrays on lamellae analogues from a hard polymer and demonstrated that adhesion on non-planar surfaces was five times greater than arrays without lamellar support structures (Lee et al, 2009). Our results suggest that adhesion to rough surfaces of these gecko-inspired adhesives may be improved if the relative size between the adhesive geometry and surface geometry is carefully considered.…”
Section: Research Articlementioning
confidence: 99%
“…The incorporation of exclusively 'dry' components , a quick-release mechanism (Russell, 2002), near-indefinite reusability, and self-cleaning (Hansen and Autumn, 2005) make gecko adhesion mechanics interesting not just to researchers in the natural sciences but also to those in engineering disciplines. There are numerous research programs aimed at fabricating gecko-like synthetic adhesives (GSAs) that reproduce the important features of the gecko system Geim et al, 2003;Lee et al, 2009;Mahdavi et al, 2008;Murphy et al, 2007;Sitti and Fearing, 2003).…”
Section: Introductionmentioning
confidence: 99%